Attitudes of nursing staff related to the nursing process - Guedes, Erika de Souza; Turrini, Ruth Natália Teresa; Sousa, Regina Márcia Cardoso de; Baltar, Valéria Troncoso; Cruz, Diná de Almeida Lopes Monteiro da (Revista da Escola de Enfermagem da USP, 2012)
The aims of the study were to describe nurses' positions on nursing process and their perception of power; and to analyse associations between positions on nursing process, power perception and selected variables. One thousand six hundred and five nurses (86.9% female, mean age=44.12 years, SD=9.55) participated in the study. Mean score on the Positions on Nursing Process (PNP) tool was 112.37 (SD=22.28); and on the Power as Knowing Participation in Change Tool - Brazilian Version (PKPCT) was 281.12 (SD=38.72). Baccalaureate nurses had statistically higher scores on PNP and PKPCT than auxiliary nurses. There was positive and moderate correlation between PNP and PKPCT scores. Auxiliary nurses' scores on PNP were associated with sex and post-graduation; auxiliary nurses' scores on PKPCT were associated with sex. For baccalaureate nurses there was association between PKPCT and administrative position. More studies should be developed in order to identify variables potentially associated with the use of nursing process in clinical practice.